(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Pediatric fractures of the neck of femur are rare but potentially devastating injuries due to the high risk of avascular necrosis (AVN), nonunion, and premature physeal closure. Optimal management remains controversial due to limited case numbers and heterogeneity in treatment protocols. Objective: To evaluate management strategies and clinical outcomes of pediatric femoral neck fractures (PFNFs) and to analyze factors influencing complications. Methods: A retrospective observational analytical study conducted at a tertiary care teaching hospital reviewing cases treated between August 2019 and December 2024. Demographic characteristic, fracture classification (Delbet), timing of surgery, fixation method, and complications were recorded. Functional outcome was assessed using Ratliff’s criteria. Statistical analysis was performed using SPSS version 25.0 (IBM Corp., Armonk, NY, USA). Associations were analyzed using Chi-square test and logistic regression. Results: Forty-two patients (mean age 11.2 ± 3.4 years) were analyzed, with Delbet Type II fractures being most common (40.5%). The overall AVN rate was 19%, while nonunion and premature physeal closure was observed in 9.5% and 14.2% cases, respectively. Early surgery (<24 hours) significantly reduced AVN incidence (p=0.03), and delayed intervention was an independent predictor of AVN (OR: 2.8, 95% CI: 1.1–6.9). Closed reduction yielded superior functional outcomes compared to open reduction (p=0.04).This finding may reflect fracture severity selection rather than superiority of technique. Conclusion: Early anatomical reduction and stable internal fixation significantly reduce complications in pediatric femoral neck fractures. Prompt surgical management within 24 hours remains critical to minimize AVN and improve functional outcomes.